2015
DOI: 10.1080/10408398.2013.859563
|View full text |Cite
|
Sign up to set email alerts
|

Quality properties of fruits as affected by drying operation

Abstract: The increasing consumption of dried fruits requires further attention on the quality parameters. Drying has become necessary because most fruits are highly perishable owing to their high moisture content and the need to make them available all year round and at locations where they are not produced. In addition to preservation, the reduced weight and bulk of dehydrated products decreases packaging, handling and transportation costs. Quality changes associated with drying of fruit products include physical, sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 166 publications
3
59
1
1
Order By: Relevance
“…For freeze‐dried samples, the rehydration ratio increased significantly within the first 60 min and remained approximately constant afterwards. Rapid initial water uptake of freeze‐dried samples was reported in literature (Omolola et al, ). Ergun et al () determined the rehydration behavior of freeze‐dried kiwi fruit slices in distilled water at a temperature of 18 °C and reported that freeze‐dried samples rapidly absorbed water and the moisture content of sample stayed nearly constant after 15 min of rehydration.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…For freeze‐dried samples, the rehydration ratio increased significantly within the first 60 min and remained approximately constant afterwards. Rapid initial water uptake of freeze‐dried samples was reported in literature (Omolola et al, ). Ergun et al () determined the rehydration behavior of freeze‐dried kiwi fruit slices in distilled water at a temperature of 18 °C and reported that freeze‐dried samples rapidly absorbed water and the moisture content of sample stayed nearly constant after 15 min of rehydration.…”
Section: Resultsmentioning
confidence: 81%
“…The drying technique affects the nutritional quality like ascorbic acid content, total phenolic content (TPC) of the fruits (Izli, Izli, & Taskin, ; Kamiloglu et al, ). In addition to nutritional quality, other quality parameters of fruits such as color, texture, porosity, and rehydration ability are affected by the drying process (Omolola, Jideani, & Kapila, ). In literature, most of the studies conducted on the drying of kiwi fruit includes only the HAD method and investigates the effect of HAD parameters (temperature, air velocity, relative humidity) or the sample properties (thickness, initial moisture content) on product quality (Chin, Siew, & Soon, ; Kaya, Aydın, & Kolayli, ; Mahjoorian et al, ; Mohammadi, Rafiee, Djomeh, & Keyhani, ).…”
Section: Introductionmentioning
confidence: 99%
“…Selected dried fruits, rich in specific compounds, such as amla fruits or Indian gooseberries, avocados, berries, mangoes, mangosteens, persimmons, prunes, raisins, and kiwi fruits, may also present cancer chemopreventive effects [159].…”
Section: Health Benefits Of Functional Dehydrated Foodsmentioning
confidence: 99%
“…It has become necessary because most fruits are highly perishable owing to their high moisture content and the need to make them available all year round and at locations where they are not produced. In addition to preservation, the reduced weight and bulk of dehydrated products decreases packaging, handling and transportation costs (Omolola et al 2017). There are many investigations on hot air drying, vacuum drying, freezing drying and heat pump drying (HPD) systems to improve drying quality and energy efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The pineapple (Ananascomosus) is a tropical plant with an edible multiple fruit consisting of coalesced berries, also called pineapples (Morton 1987;Omolola et al 2017). Pineapples can be consumed fresh, cooked, juiced, or preserved.…”
Section: Introductionmentioning
confidence: 99%